PENANAMAN MODAL SEBAGAI PENGGERAK PENGUATAN HUKUM DAN PEMBANGUNAN EKONOMI - Fadhilah, Muhammad (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2021)
When we discuss that Indonesia is an archipelagic country that is very rich and examines its natural products, it also examines the tasks of the government and the state, both in terms of written legal rules in the constitution or rules collected in constitutional law to effectively carry out Indonesia's natural resources. have. Considering that Indonesia is a state based on law, the State Administration Law (HAN) and Investment Law are needed as instruments for implementing governmental power. This study accommodates two problems, namely the definitive limits of Investment regulations, policies and decisions according to HAN and the principles and norms of HAN in making regulations, policy regulations, and decisions. This research was conducted with a normative legal approach or legal literature study. The results of this study state that a regulation is a law that is abstract or general norm which is generally binding (generally accepted) and its task is to regulate general matters. While policy regulations only function as part of the operational tasks of government, they cannot change or deviate from statutory regulations.